The Anatomy of Truth in European Conservation Movement: Traditions and Perspectives - Špikić, Marko (Array, 2014)
This presentation focuses on some of the key issues in conservation and restoration in the past century and a half: maintaining, or creating, the authentic set of messages in cultural heritage. Discussing about the truth in conservation is as ambitious as contemplating on the role of time (in Yourcenar’s vision of its force) and of inheritors, that is of the generations of women and men deciding on the destiny of monuments and sites. Philosophical questions on truth, that motivated thinkers from the Antiquity, found their firm place in Modern Conservation Movement even before John Ruskin’s times. From that period we can follow the professional and public debate on values, choices, tolerance and discriminations that shaped European citizens’ identities. Even though European history of conservation became a firm genre in the past fifty years, seldom have this questions been discussed in a comparative approach. I will therefore deal with the perception of truth, the importance of the principle of transformation of the monument’s image in the passing of time, and the urge of professionals, politicians and communities to physically intervene, following their sense of the past and interpreting of monuments’ authentic meaning.